Bibliometric Analysis of Publications in the Field of Legal Medicine from Turkey - Zeybek, Volkan; Karabağ, Gökmen; Yavuz, M. Sunay (The Bulletin of Legal Medicine, 2022)
Aim: In this bibliometric study, it was aimed to analyze the topics, change in number of publications, citations and journals in which they were published in legal medicine articles from Turkey over a 40-year period.Material Methods: Publications between 1980 and 2020 included in Web of Science databases were evaluated. In WoS database, by writing “legal medicine” in web of science category (WC) field and “Turkey” in country field, all indexes in WoS were included and years 1980-2020 were selected, and only those with ‘article’ were included in the search.Results: It was understood that there were 613 articles in field of legal medicine from Turkey, the most publications (10%) were in 2016, and the journal in which the most articles were published was "Forensic Science International". The articles received a total of 6202 citations, with the most citations in 2020 with 760 (12.2%) citations. It was observed that the most frequently used keywords were “forensic science” (21.8%), “autopsy” (10.9%) and “Turkey” (8.4%). Looking at the institutions to which the authors are affiliated; it was seen that 879 (57.1%) were universities in Turkey, 194 (12.6%) were the Ministry of Justice, 134 (8.8%) were the Ministry of Health.Conclusions: Despite the difficulties experienced in the field of legal medicine over years, it has been revealed that number of studies in this field has increased and citations to these studies have increased.
Keywords: Legal medicine; bibliometric analysis; Turkey